The Development of the American Family Farms and the Enlightenment to China -- Based on data from the Four the U.S. Agricultural Censuses from 1997 to 2012 - Ye Deng; Zilan Song; Yuetao Yao (International Journal of Engineering and Management Research, 2020)
Based on the data of four agricultural census of the United States from 1997 to 2012 and relevant data, this paper has summarized the development and the status quo of the American farms. According to the reality of china’s agricultural development, some suggestions are put forward. First, giving priority to cultivate and develop large-scale business entities. Second, perfecting agricultural socialized service system actively, and fostering subsequent forces agricultural field. On September 26, 2018, the CPC Central Committee and the State Council issued the Strategic Plan for Rural Revitalization (2018-2022), which set out the relevant development requirements of “establishing a modern agricultural operation system, strengthening new types of agricultural operation entities, and facilitating the organic connection between the production of small farmers and the development of modern agriculture”. As a new type of main business entity in China, family farm has been developing rapidly. By the end of 2012, China had 877,000 family farms with 176 million mu of cultivated land managed, accounting for 13.4 % of the country’s contracted arable land. On the whole, however, family farms are still in the initial stage of exploration and development, and many aspects still need to be further improved. This paper summarizes the development of American family farms by using the data of the US agricultural Census from 1997 to 2012, the annual statistics of the US agriculture in 2017 and other relevant data, and analyzes the enlightenment of the US experience to China based on the actual situation of China, so as to provide references for the development of Chinese family farms.